An Examination of the Intersection of Climate Change, the Physician Specialty Workforce, and Graduate Medical Education in the U.S. Issue 3 (14th June 2022) - Colbert, Colleen Y.; French, Judith C.; Brateanu, Andrei; Pacheco, Susan E.; Khatri, Sumita B.; Sapatnekar, Suneeti; Vacharathit, Voranaddha; Pien, Lily C.; Prelosky-Leeson, Allison; LaRocque, Regina; Mark, Bryan; Salas, Renee N.
Abstract: Issue: As U.S. healthcare systems plan for future physician workforce needs, the systemic impacts of climate change, a worldwide environmental and health crisis, have not been factored in. The current focus on increasing the number of trained physicians and optimizing efficiencies in healthcare delivery may be insufficient. Graduate medical education (GME) priorities and training should be considered in order to prepare a climate-educated physician workforce. Evidence: We used a holistic lens to explore the available literature regarding the intersection of future physician workforce needs, GME program priorities, and resident education within the larger context of climate change. Our interinstitutional, transdisciplinary team brought perspectives from their own fields, including climate science, climate and health research, and medical education to provide recommendations for building a climate-educated physician workforce. Implications: Acknowledging and preparing for the effects of climate change on the physician workforce will require identification of workforce gaps, changes to GME program priorities, and education of trainees on the health and societal impacts of climate change. Alignment of GME training with workforce considerations and climate action and adaptation initiatives will be critical in ensuring the U.S. has a climate-educated physician workforce capable of addressing health and healthcare system challenges. This article offers a number of recommendations for physician workforce priorities, resident education, and system-level changes to better prepare for the health and health system impacts of climate change.